2023
DOI: 10.3389/fnins.2023.1106570
|View full text |Cite|
|
Sign up to set email alerts
|

Increased central auditory gain in 5xFAD Alzheimer’s disease mice as an early biomarker candidate for Alzheimer’s disease diagnosis

Abstract: Alzheimer’s Disease (AD) is a neurodegenerative illness without a cure. All current therapies require an accurate diagnosis and staging of AD to ensure appropriate care. Central auditory processing disorders (CAPDs) and hearing loss have been associated with AD, and may precede the onset of Alzheimer’s dementia. Therefore, CAPD is a possible biomarker candidate for AD diagnosis. However, little is known about how CAPD and AD pathological changes are correlated. In the present study, we investigated auditory ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(39 citation statements)
references
References 118 publications
3
33
0
Order By: Relevance
“…In the MGB of APP/PS1 mice, similar to the IC, the microglia density increase was not signi cant (Figure 3A top panel; B, left graph). The CD68+ microglia proportion showed a signi cant increase in this genotype (Figure 3A middle panel; B right graph), even though signi cant levels amyloid-β plaque was not detected in our previous assay (Na et al, 2023). With the higher resolution images presented here, it is clear that the CD68+ cells are associating with the low levels of plaque present (Figure 3).…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…In the MGB of APP/PS1 mice, similar to the IC, the microglia density increase was not signi cant (Figure 3A top panel; B, left graph). The CD68+ microglia proportion showed a signi cant increase in this genotype (Figure 3A middle panel; B right graph), even though signi cant levels amyloid-β plaque was not detected in our previous assay (Na et al, 2023). With the higher resolution images presented here, it is clear that the CD68+ cells are associating with the low levels of plaque present (Figure 3).…”
Section: Resultsmentioning
confidence: 51%
“…Multiple lines of evidence suggested that neuroin ammation might be the link between AD and the central auditory hyperactivity in 5xFAD mice. First, we previously performed a comprehensive examination on amyloid-b plaque deposition in the central auditory system of the 5xFAD mice, and found that amyloid-b plaque was prominent in the upper auditory brainstem of 5xFAD mice (Na et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, much of this characterization is performed later in disease progression, not capturing functional changes at earlier disease points preceding synapse loss [104,105]. Molecular and functional investigation that has been carried out in early to mid-disease mostly consists of swiftly-progressing genetic models of AD that preclude the use of littermate controls [36][37][38][39][40][41][42]. To detect and systematically investigate mechanisms of compensatory plasticity, it is essential to use a well-charted model with appropriately-matched non-transgenic controls.…”
Section: Cholinergic Signalling and Synapses In Admentioning
confidence: 99%